The proteomic profile of whole and glandular saliva in healthy pain-free subjects - Jasim, Hajer; Olausson, Patrik; Hedenberg-Magnusson, Britt; Ernberg, Malin; Ghafouri, Bijar (Scientific reports, 2016)
Determination of the variability in the salivary proteome is a prerequisite for the development of saliva as a diagnostic and prognostic tool in particular physiological states. In this context, it is important that technical variability induced by sample collection and processing is kept at minimum to be able to reproducibly assess variability in states of health and disease. In the current study, the proteome profile in unstimulated and stimulated whole, parotid and sublingual saliva was investigated using two-dimensional gel electrophoresis. Saliva samples were structurally collected from ten examined and characterized healthy individuals during the exactly same conditions. The results demonstrated that different collection methods provide clear differences in the snapshot of the salivary proteome and also in the relative amount of specific proteins. The variable nature of the salivary proteome suggests that different approaches may have to be adopted when studying its composition or its possible role as an indicator for particular physiological states. The results emphasize the importance of consistency when collecting saliva samples for proteomic analysis.